2014
DOI: 10.1016/j.shaw.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Wet-work Exposure: A Main Risk Factor for Occupational Hand Dermatitis

Abstract: Wet-work can be defined as activities where workers have to immerse their hands in liquids for >2 hours per shift, or wear waterproof (occlusive) gloves for a corresponding amount of time, or wash their hands >20 times per shift. This review considers the recent literature on wet-work exposure, and examines wet-work as a main risk factor for developing irritant contact dermatitis of the hands. The aim of this paper is to provide a detailed description of wet-work exposure among specific occupational groups who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
102
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 59 publications
5
102
2
9
Order By: Relevance
“…It was found that ironing workers are repeatedly exposed to hot and humid conditions, which cause and aggravate dermatitis. [29] …”
Section: Discussionmentioning
confidence: 99%
“…It was found that ironing workers are repeatedly exposed to hot and humid conditions, which cause and aggravate dermatitis. [29] …”
Section: Discussionmentioning
confidence: 99%
“…These areas are more frequently exposed to possible occupational skin irritants in the water such as chlorine compounds and disinfection byproducts. Chronic exposure to water has been associated with contact dermatitis among workers who perform "wet work" [Behroozy and Keegel 2014;Meding 2016]. Lifeguards rotate through stations where they might be immersed in water up to thigh level.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic contact dermatitis (ACD), a type IV hypersensitivity reaction, is common among certain occupational groups such as those regularly exposed to chemicals or involved in wet work (Behroozy and Keegel, 2014). However, also cosmetics and household products can contain numerous skin sensitizing chemicals.…”
Section: Introductionmentioning
confidence: 99%